2015
DOI: 10.1042/bj20150213
|View full text |Cite
|
Sign up to set email alerts
|

HOXB5 induces invasion and migration through direct transcriptional up-regulation of β-catenin in human gastric carcinoma

Abstract: HOX (homeobox) genes encode a family of transcriptional regulators, which have an important role in morphogenesis and differentiation during embryonic development. Their deregulated expression is involved in the carcinogenesis of many human solid tumours. In the present study, we show that HOXB5 mRNA was significantly overexpressed in gastric cancer tissues compared with adjacent normal tissues. HOXB5-up-regulated cancer cells showed increased invasion and migration activity, but no change in proliferation act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 40 publications
2
38
0
2
Order By: Relevance
“…Multiple studies have highlighted the key role of the Wnt signaling pathway in carcinogenesis and neoplastic transformation of different forms of human cancer, including gastric cancer (48), colorectal cancer (45), breast cancer (19), and prostate cancer (17,22). HOX genes, including both HOXA13 and HOXB5, are able to participate in cancer development by activating the Wnt/␤-catenin signaling pathway (15,20). Interestingly enough, HOXB7 was identified as being an upregulated gene in CSCC based on the microarray data provided by the GSE66359 profile, which supported our hypothesis that HOXB7 might have participated in the regulation of CSCC.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have highlighted the key role of the Wnt signaling pathway in carcinogenesis and neoplastic transformation of different forms of human cancer, including gastric cancer (48), colorectal cancer (45), breast cancer (19), and prostate cancer (17,22). HOX genes, including both HOXA13 and HOXB5, are able to participate in cancer development by activating the Wnt/␤-catenin signaling pathway (15,20). Interestingly enough, HOXB7 was identified as being an upregulated gene in CSCC based on the microarray data provided by the GSE66359 profile, which supported our hypothesis that HOXB7 might have participated in the regulation of CSCC.…”
Section: Introductionmentioning
confidence: 99%
“…Such as, HOXB5 is overexpressed in human gastric carcinoma and induces invasion and migration through direct transcriptional up-regulation of β-catenin (Hong et al 2015), and HOXB5 is aberrantly overexpressed in breast cancer tissues and cell lines and promotes proliferation and invasion of breast cancer cells (Lee et al 2015). Moreover, Luo et al reported that HOXB5 was frequently over-expressed both in bladder cancer tissues and cell lines and inhibition of HOXB5 suppressed the oncogenic function of cancer cells (Luo et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…We discover that HOXB5 is a direct target of miR-1275, and is up-regulated in several tumors, including gastric carcinoma (Hong et al 2015), breast cancer (Lee et al 2015), bladder cancer (Luo et al 2012), and oral squamous cell carcinoma (Tucci et al 2011). While whether HOXB5 is up-regulated in NPC is not be explored.…”
Section: Introductionmentioning
confidence: 99%
“…The Wnt/β-catenin signaling regulates cell viability, growth, apoptosis, and invasion in various types of cancer, including glioma [28][29][30], and inhibiting this pathway decreased viability and increased apoptosis of adrenocortical tumor cells [28]. Pharmacological or genetic inhibition of Wnt activity augmented the effects of alkylating drugs and restored chemosensitivity in different cancers.…”
Section: Klf8 Modulates Glioma Chemosensitivity To Tmz In Vivomentioning
confidence: 99%